Multicentre clinical radiotherapy audit in rectal cancer: results of the IROCA project - Magdalena Fundowicz; Artur Aguiar; Carla Lopes de Castro; Maria Glòria Torras; Letizia Deantonio; Ewelina Konstanty; Marta Kruszyna-Mochalska; Miquel Macia; Eugeni Canals; Monica Caro; Carla Pisani; Dorota Zwierzchowska; et al. (Radiation Oncology, 2020)
Abstract Purpose To perform a clinical audit to assess adherence to standard clinical practice for the diagnosis, treatment, and follow-up of patients undergoing radiotherapy for rectal cancer treatment in four European countries. Materials and methods Multi-institutional, retrospective cohort study of 221 patients treated for rectal cancer in 2015 at six European cancer centres. Clinical indicators applicable to general radiotherapy processes were evaluated. All data were obtained from electronic medical records. Results The audits were performed in the year 2017. We found substantial inter-centre variability in adherence to standard clinical practices: 1) presentation of cases at departmental clinical sessions (range, 0–100%) or multidisciplinary tumour board (50–95%); 2) pretreatment MRI (61.5–100%) and thoracoabdominal CT (15.0–100%). Large inter-centre differences were observed in the mean interval between biopsy and first visit to the radiotherapy department (range, 21.6–58.6 days) and between the first visit and start of treatment (15.1–38.8 days). Treatment interruptions ≥ 1 day occurred in 43.9% (2.5–90%) of cases overall. Treatment compensation was performed in 2.1% of cases. Treatment was completed in the prescribed time in 55.7% of cases. Conclusions This multi-institutional clinical audit revealed that most centres adhered to standard clinical practices for most of the radiotherapy processes-related variables assessed. However, the audit revealed marked inter-centre variability for certain quality indicators, particularly inconsistent record keeping. Multiple targets for improvement and/or harmonisation were identified, confirming the value of routine clinical audits to detect potential deviations from standard clinical practice.